Naropa : the indian buddhist mystic - Lhamo, Jungney (New Delhi : Heritage Publishers, 2015)
The great Siddha Naropa is a deeply revered Buddhist teacher. He lived in India in the eleventh century. Naropa was among the enlightened teachers of the Kagyu lineage of Tiberan Buddhism. Before becoming a spiritual teacher, Naropa was an undefeatable scholar at the Nalanda University, the place where he first felt the vibration of the name, Tilopa. Naropa was born in a respectable Brahmin family that had considerable power and riches at their disposal. Tilopa laid the foundation of Naropa's spiritual life and became his root Guro. The story of Naropa expresses complete surrender and an unfailing belief in one's guru or master so that a student can become in sync with his master's mind.
Keywords: Buddhist masters